Child-Oriented or Parent-Oriented Focused Intervention: Which is the Better Way to Decrease Children's Externalizing Behaviors? - Roskam, Isabelle; Brassart, Elise; Houssa, Marine; Loop, Laurie; Mouton, Bénédicte; Volckaert, Alexandra; Nader-Grosbois, Nathalie; Noël, Marie-Pascale; Schelstraete, Marie-Anne (Journal of Child & Family Studies, 2017)
Research has tried to identify risk factors that increase the likelihood of difficulties with externalizing behavior. The relations between individual or environmental factors and externalizing behavior have been especially documented. Child-oriented and parent-oriented interventions have been designed in order to decrease externalizing behavior in preschoolers. To date, however, research has largely been compartmentalized. It is therefore not known whether child-oriented or parent-oriented intervention is more effective in reducing externalizing behavior. The aim of the current study was to answer this question by comparing two 8-week child with two 8-week parent-oriented group programs sharing a common experimental design. This was done in a pseudo-randomized trial conducted with 73 3-6-year-old children displaying clinically relevant levels of externalizing behavior who were assigned to one of the four interventions and 20 control participants who were allocated to a waiting list. The results indicate that the four programs focusing on a specific target variable, i.e., social cognition, inhibition, parental self-efficacy beliefs, or parental verbal responsiveness, are all effective in reducing externalizing behavior among preschoolers. Their effectiveness was moderated neither by their orientation toward the child or the parent nor by their content, suggesting that several effective solutions exist to improve behavioral adaptation in preschoolers. A second important highlight of this study is that, thanks to comparable effect sizes, brief focused programs appear to be a reasonable alternative to long multimodal programs, and may be more cost-effective for children and their families.